GAMBARAN TINGKAT PENGETAHUAN GIZI OLAHRAGA, FREKUENSI MINUM MINUMAN ISOTONIK, KEBUGARAN JASMANI, DAN STATUS GIZI PADA ATLET SEPAKBOLA DI DIVISI UTAMA PERSATUAN SEPAKBOLA LANGKAT (PSL) BAPOR PERTAMINA PANGKALAN SUSU TAHUN 2017 - Tri Nanda Putri; Albiner Siagian; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The game of football is a sport that requires physical endurance and intensity high so that a good nutritional status is required as well as enough nutrients to support performance and the performance of the athletes. The need to maintain fluid balance in the body, because if the lack of fluid consumption can lead to dehydration which can degrade the performance of the sport. This research was conducted to find out the description of the level of knowledge of sports nutrition, the frequency of drinking fitness isotonic drink, physical, and nutritional status in football athletes at Premier Division Persatuan Sepakbola Langkat (PSL) Bapor Pertamina Pangkalan Susu. This research uses a cross-sectional design with sampling technique using total sampling. Sport nutrition knowledge measurement using questionnaires, frequency beverages isotonic method using a Food Frequency Questionnaire, physical fitness test method using balke, and nutritional status using the method of anthropometry. Then data analyzed are descriptive. The results showed that athletes have knowledge of sports nutrition less 53,3%, do not consume drinks isotonic 40,0%, enough physical fitness 66,7%, and status malnutrition 56,7%. It is recommended that the athlete applying a good diet and healthy to optimize intake of energy and nutrients your body needs to improve performance fitness athletes in sports. Keywords :Nutrition Sports, Isotonic Drink, Fitness, Nutritional Status ofFootball Athlete